ANALISIS CREATIVE ACCOUNTING SEBAGAI VARIABEL MODERASI DALAM PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Nahar, Aida; Auliyak, Ishar (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This study aims to analyze creative accounting as a variable that strengthens the influence of corporate social responsibility on the financial performance of companies with the LQ45 index for the 2018-2019 periods. This study uses secondary data from the financial statements of companies incorporated in LQ45 in 2018-2019. The population in this study is a company with an LQ45 index that publishes financial statements in rupiah currency in 2018 and 2019. The sampling technique used is saturated sampling, which means that the entire population is used in all samples. Based on the data, there are 38 companies. The data analysis method used classical assumption test and Moderating Regression Analysis (MRA). The results of this study indicate that corporate social responsibility individually does not affect financial performance, but the presence of creative accounting can strengthen the influence of corporate social responsibility on financial performance.